Diversity of Play - Fuchs, Mathias (meson press, 2015)
The early days when digital games were new, harmless, and a niche are long gone. Today's games can simulate battlefields, predict disaster, and crash markets. We are faced with a diversity of play and the ubiquity of games, making them not only a popular medium, but the leading medium of our contemporary society. Based on the keynote lectures held at DiGRA2015, "Diversity of Play" provides a critical view on the current stage of digital games from a theoretic, artistic, and practical perspective by pointing towards the uncanny, the power of "unnatural" narratives, and the exceptions and uncertainties of digital ludic environments. With an interview with Karen Palmer and essays by Astrid Ensslin, Mathias Fuchs, Tanya Krzywinska, and Markus Rautzenberg.